BENTUK DAN FUNGSI DEIKSIS DALAM TAJUK RENCANA PADA SURAT KABAR SOLOPOS EDISI 2017 DAN RELEVANSINYA SEBAGAI BAHAN AJAR PEMBELAJARAN TEKS EDITORIAL DI SEKOLAH MENEGAH ATAS - Meilda Maharani Purwandari; Ani Rakhmawati; Slamet Mulyono (Universitas Sebelas Maret, 2019)
This Analysis explain and describe: (1) the forms of deixis contained in the editorial of Solopos edition 2017; (2) the use of the deixis function in the editorial of Solopos edition 2017; (3) its relevance as teaching material of editorial text in high school. This research is a qualitative descriptive research with source data derived from editorial paper Solopos Edition 2017. Sampling technique of this research using purposive sampling and using document analysis and interview. Technique of data validity test that used is triangulation theory. The results of this research are 1) found 5 deixis form namely, deixis persona, deixis place/ space, deixis time, deixis discourse, and social deixis; 2) Based on the analysis found the functions of the use of deixis at Solopos Editorial Edition 2017 a) the function deiksis persona, b) The deixis function of place, c) The time dextis function, d) the function of the discourse of discourse, e) the social deixis function; 3) The Editor's editorial in the 2017 edition of Solopos matching with the criteria as teaching material for editorial texts in high school.